The Development of Ideas for Reform and Transformation of Islamic Family Law Becoming Legislation in Islamic Countries - Yuzaini, Zakia; Candra, Afrikal; Mulyani, Ridha; Fadli Rambe, Khairul; Sasralina, Rika; Ilman Nafian, Zidni (Samara: Journal of Islamic Law and Family Studies, 2024)
Family law reform in Muslim countries remains a subject of debate among the global Muslim community because they believe that Islamic family law and family law are not equal.   This article aims to examine the renewal and transformation of family law in the Islamic world. This research is a literature review, with a descriptive-analytical research type. The approach used is interdisciplinary, namely comparative, legal, philosophical, and historical. The sources of this research include primary sources such as law books and secondary sources such as theses, dissertations, and journal articles. The factors influencing the renewal of Islamic family law in the world are politics, economics, and social law.  The methods of Islamic legal reform are siyasyah al-shar'iyyah, takhayyur, takhsis al-qhadha, the old theory of ijtihad, ijma, qiyas, maslahah mursalah, and sadd' al-dhari'ah. The renewal of Islamic law in the world includes polygamy, inheritance, marriage registration, and marriage contracts. The transformation of Islamic family law in Indonesia is reflected in Law Number 1 of 1974 on Marriage, State Gazette No. 1 of 1974, Supplement No. 3019/1974. Presidential Instruction No. 1 of 1991 on the Compilation of Islamic Law, which serves as the standard reference for judges in adjudicating cases. The 2002 Law on Child Protection, Law No. 23 of 2004 on Domestic Violence, Law No. 12 of 2022 on Sexual Violence Crimes, and  the  legislation  are in line with Islamic family law.